SAT0157 The sex hormone binding globulin in male osteoporosis. (1st June 2001) - Legrand, ER; Gibert, C; Gallois, Y; Mathieu, E; de casson, F Boux; Basle, MF; Chappard, D; Audran, M
Abstract : Background: Several studies have shown that the increase in Sex Hormone Binding Globulin and the decrease in biovailable estradiol and testosterone can explain age-induced bone loss in healthy men over 70 years. Objectives: To evaluate the role of the Sex Hormone Binding Globulin (SHBG) in the pathophysiology of osteoporosis in middle-aged men. Methods: 80 men with osteoporosis (T-score < -2.5) and 40 age-matched controls were recruited to evaluate the relationships between sex hormone levels, bone markers levels, bone mineral density and vertebral fractures. Fasting serum samples were assayed for total and free testosterone, total estradiol and SHBG. Bone remodelling was evaluated by measurement of urinary levels of the C-telopeptide of type I collagen (CTX) and free deoxypyridinoline (D-Pyr), serum osteocalcin and bone specific alkalin phosphatase (BSAP). Results: There was no difference between controls and osteoporotic men according to age, BMI, total testosterone and estradiol. In contrast, serum SHBG level was significantly higher (+ 42.2%) whereas free androgen index was lower (- 24.8%) in patients with osteoporosis. Stepwise linear regression analysis showed that SHBG was significantly correlated with D-Pyr (r = 0.33), CTX (r = 0.25) and BSAP (r = 0.30). (3) After adjustment for age and BMI, hip BMD was not associated with total testosterone or estradiol but only with serum SHBG (r = – 0.35). (4) Among osteoporotic patients, spinal radiographs evidenced at least one vertebral crush fracture in 36 men and none in 44 patients. Serum SHBG concentration was significantly associated with the presence of vertebral fracture: odds ratio was 2.0 (95% CI: 1.2–3.5) for an increase of one standard deviation of SHBG. Conclusion: The present study showed that serum SHBG concentration is increased in most middle-aged men with primary or secondary osteoporosis and is correlated with bone remodelling markers, hip bone mineral density and vertebral fracture risk. These results might represented a plausible explanation of bone loss in young and middle-aged men with idiopathic osteoporosis and vertebral fractures.